We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
30
2
avatar+248 

Simplify $\frac{2m+8}{3}-\frac{2-m}{3}$.

Thanks!

 Jun 12, 2019
 #1
avatar+8207 
+2

\(\frac{2m+8}{3}-\frac{2-m}{3}\ =\ \frac{(2m+8)-(2-m)}{3}\ =\ \frac{2m\,+\,8\,-\,2\,+\,m}{3}\ =\ \frac{3m+6}{3}\,=\,\frac{3m}{3}+\frac63\ =\ m+2\)_

 Jun 12, 2019
 #2
avatar+248 
+1

Thanks!

sinclairdragon428  Jun 12, 2019

7 Online Users

avatar